Seismic risk assessment and design of tourism buildings using probability analysis. (2018) - Tsai, Chung-Hung
The average recurrence interval of major earthquakes is approximately a century. Consequently, the existing data are insufficient for an accurate estimation of average losses. The main objective of this research is to study the disaster-prone characteristics of hotels by using modern concepts of risk management (i.e., loss exceedance probability analysis, seismic hazard analysis and so on) and then combine the relevant basic research data from domestic and foreign sources to develop a seismic risk assessment and management system suitable for the hospitality industry. The proposed seismic risk management and risk evaluation system will also provide governments, hotel asset owners, insurance companies and banks in Taiwan that have similar regional characteristics with the necessary seismic risk information to help the tourism industry effectively evaluate and manage the natural disaster risk.